One-pot synthesis of biodegradable polydopamine-doped mesoporous silica nanocomposites (PMSNs) as pH-sensitive targeting drug nanocarriers for synergistic chemo-photothermal therapy. Issue 65 (7th November 2018) - Zhang, Huicong; Wang, Xuandong; Wang, Peiyuan; Liu, Rong; Hou, Xuemei; Cao, Wei; Zhong, Rong; Liu, Xiaolong; Zhang, Yun
Abstract : Polydopamine-doped mesoporous silica nanocomposites (PMSNs) were controllably synthesized by a one-pot approach. They were demonstrated to be good biodegradability, pH-responsive drug release and targeting synergistic chemo-photothermal therapy. Abstract : Nanomaterials have been widely used as drug carriers in the biomedical field. However, most of them have limited application because of their poor biocompatibility, targeting, and degradability. Therefore, exploring and developing novel drug nanocarriers to overcome these problems has widely attracted attention. In this study, polydopamine-doped mesoporous silica nanocomposites (PMSNs) were controllably synthesized by a one-pot oil-water biphase stratification approach. PMSNs showed good biodegradability in degradation experiments and also proved to have superior biocompatibility toward hepatocellular carcinoma cells (HepG2) compared with mesoporous silica nanoparticles (MSNs). And PMSNs loaded doxorubicin (DOX) (PMSNs@DOX) exhibited a pH-responsive release effect. Meanwhile, compared with PMSNs@DOX, folic acid-modified PMSNs@DOX (PMSNs@DOX@FA) displayed a targeted uptake and higher inhibition of HepG2 cells. Additionally, PMSNs@DOX@FA had excellent ability to kill tumor cells under synergistic chemo-photothermal therapy. Moreover, this synthetic strategy is promising for the fabrication of unique nanocomposites with various functional cores with PMSNs shells for diverse applications.